2019
DOI: 10.1177/0261192919885578
|View full text |Cite|
|
Sign up to set email alerts
|

The Relevance ofIn Silico,In Vitroand Non-human Primate Based Approaches to Clinical Research on Major Depressive Disorder

Abstract: Major depressive disorder (MDD) is the most severe form of depression and the leading cause of disability worldwide. When considering research approaches aimed at understanding MDD, it is important that their effectiveness is evaluated. Here, we assessed the effectiveness of original studies on MDD by rating their contributions to subsequent medical papers on the subject, and we compared the respective contribution of findings from non-human primate (NHP) studies and from human-based in vitro or in silico rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…[ 9,19,21,22,57,58 ] The presence of different behavioral responses of individuals of this species of primate under conditions of mild stress has been noted by various authors, both in individuals living in the wild, [ 15 ] and individuals placed individually in the room. [ 13,17,59 ] Studies along these lines have shown that young adult female rhesus monkeys with DAB or SB show no intergroup differences in response of the HPA axis to the ASE (restraint for 2 h begun at 15 h) ( Figure 3 ). [ 9,19,57 ] Differences, however, do appear in response to the same stressor repeated for 10 days.…”
Section: Individual and Age‐related Features Of Hpa Axis Response To mentioning
confidence: 99%
“…[ 9,19,21,22,57,58 ] The presence of different behavioral responses of individuals of this species of primate under conditions of mild stress has been noted by various authors, both in individuals living in the wild, [ 15 ] and individuals placed individually in the room. [ 13,17,59 ] Studies along these lines have shown that young adult female rhesus monkeys with DAB or SB show no intergroup differences in response of the HPA axis to the ASE (restraint for 2 h begun at 15 h) ( Figure 3 ). [ 9,19,57 ] Differences, however, do appear in response to the same stressor repeated for 10 days.…”
Section: Individual and Age‐related Features Of Hpa Axis Response To mentioning
confidence: 99%
“…It can be argued that there is a need to have a substantial amount of animal research before achieving a critical mass that can lead to useful breakthroughs in human health, which might explain the high level of citations of animal papers by subsequent animal papers. Nonetheless, it does not explain the low level of citations by human papers, especially when this does not appear to be a trend in humanbased approaches (in vitro and in silico) which received more citations by human medical papers in a small study previously conducted (Carvalho et al, 2019). Furthermore, a recent citation analysis in another field of human health research also found in vitro papers to be the most cited papers, above reviews, and animal experimentations papers (Adnan and Ullah, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…To evaluate the contribution of animal models to MDD research is important for ethical and economic reasons. As a society, we should make an informed decision on whether we should proceed improving animal models until we find a suitable one or if we should halt the current paradigm and invest more in other methods that might be more promising as well as cheaper and less ethically contentious (Carvalho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The information compiled comprises the total number of citations, and the patterns of citation. We used a total of 67 target papers of in vitro or in silico studies on MDD-utilising only human data, selected from the citation analysis database created in our previous study [6]. The citation analysis was performed between September 2016 and June 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Data obtained via simpler models (in vitro and in silico) seemed to be more visible or considered more important by the human medical research community. This called into question the contemporary paradigm of biomedical research and drug discovery, in which knowledge is presumed to transfer between animal and human models [6].…”
Section: Introductionmentioning
confidence: 99%